Objective criteria for return to athletics after anterior cruciate ligament reconstruction and subsequent reinjury rates: A systematic review - Barber-Westin,S. D.; Noyes, F. R. (The Physician and Sportsmedicine, 2011)
Objective: To review anterior cruciate ligament (ACL) clinical studies to assess the objective functional criteria used to determine when patients can return to athletics postoperatively, and to determine the rates of reinjury to either knee when these criteria are applied. Methods: A literature search was conducted using the Medline database. The inclusionary criteria were the English language, publication between April 2001 and April 2011, original clinical trials, all levels of evidence, primary ACL reconstruction, skeletal maturity, minimum 2 years of follow-up, and =1 objective test used to allow release to sports activities. The exclusionary criteria were revision ACL reconstructions or dislocated knees; studies that specifically excluded patients with ACL graft failure or reinjuries; major concomitant procedures such as high tibial osteotomy, meniscus allograft, other knee ligament reconstructions; and case reports, abstracts, review articles, and technical notes. Results: Three objective criteria were used to allow release to sports activities. The most common were lower extremity muscle strength, followed by lower limb symmetry, and knee examination parameters of range of knee motion and effusion. Twelve studies listed 1 criterion for release to sports, 8 studies listed 2 criteria, and 1 study recommended 3 criteria. Failure rates of the ACL reconstructions ranged from 0% to 3% in 7 studies, from 4% to 6% in 6 studies, from 7% to 10% in 4 studies, and from 14% to 24% in 4 studies. There were no injuries in the contralateral ACL in 14 studies (67%); in the other 7 studies, contralateral injury was reported in 2% to 15% of patients. Conclusions: Few objective functional criteria are used to determine when patients return to unrestricted sports activities. Clinically feasible recommendations are made for measurement of muscle strength, lower limb symmetry, lower limb neuromuscular control, and ligament function in patients who desire to return to athletics after ACL reconstruction. Future studies are required to determine whether the demonstration of normal lower limb function before return to sports is effective in reducing reinjury rates.